Addressing the Problems of Guidance and Counseling Teachers in Schools: An Effective Management and Supervision Approach - Robbi Asri; Neviyarni S; Firman; Rendy Amora (Manajia: Journal of Education and Management, 2025)
The problems faced by Guidance and Counseling (BK) teachers in schools are often complex and diverse, including limited resources, high workloads, and lack of support from school management. This study aims to explore effective management and supervision strategies in overcoming these problems. Through a qualitative approach, data were collected from in-depth interviews with BK teachers, principals, and BK supervisors. The results of the study indicate that transparent management, structured supervision, and ongoing professional training and development play a key role in improving the performance and welfare of BK teachers. In addition, collaboration between BK teachers and school management can strengthen support and facilitate the achievement of more holistic educational and guidance goals. The conclusion of this study provides practical recommendations for the development of a more effective management and supervision system in supporting the vital role of BK teachers in schools. The method used is a literature review with critical analysis of ongoing research on specific topics.